Biosynthesis of coelulatin for the methylation of anthraquinone featuring HemN-like radical S-adenosyl-L-methionine enzyme - Nie, Lishuang; Wei, Tianyi; Cao, Mingming; Lyu, Yunbin; Wang, Shaochen; Feng, Zhiyang (Frontiers in Microbiology, 2022)
Typically, bacterial aromatic polyketides are biosynthesized by type II polyketide synthetase. Advances in DNA sequencing, informatics, and biotechnologies have broadened opportunities for the discovery of aromatic polyketides; meanwhile, metagenomics is a biotechnology that has been considered as a promising approach for the discovery of novel natural products from uncultured bacteria. Here, we cloned a type II polyketide biosynthetic gene cluster from the soil metagenome, and heterologous expression of this gene cluster in Streptomyces coelicolor M1146 resulted in the production of three anthraquinones, two of which (coelulatins 2 and 3) have special hydroxymethyl and methyloxymethyl modification at C2 of the polyketide scaffold. Gene deletion and in vitro biochemical characterization indicated that a HemN-like radical S-adenosyl-L-methionine (SAM) enzyme CoeI exhibits methylation involved in C2 modification.